System health management with aerospace applications - Johnson, Stephen B., 1959- (Wiley, 2011)
"System Health Management with Aerospace Applications is the first reference text in its field. Due to the disparate nature of the technologies involved in Systems Health Management (SHM), no single person can understand all aspects of the discipline; hence this book collates together in one text the state-of-the-art in research and technology.System Health Management with Aerospace Applications is edited by a team of NASA based engineers and consultants, each heading up sections in their own areas of expertise and co-coordinating contributions from leading experts. The six sections include SHM and its Socio-Technical Context, SHM and the System Life Cycle, Analytical Methods, Operations, Subsystems and Systems.Key features: Authored and edited by experts from NASA and leading industry partners Collates together a wealth of information currently unpublished or disseminated throughout journal and conference papers Explains the fundamentals of each sub-discipline introduced, with a comprehensive list of references, enabling the reader to expand their knowledge base with no prior specialist experience required in the disparate areas Features real-life case studies"--